Gender and extreme metal: Understanding gender relations in the Montreal extreme metal scene with schipper's gender framework - Beauchamp, Caroline (Université Concordia, 2021)
Extreme metal is a masculine space, yet more and more women join in. They face a contradiction: as women, they are expected to adopt feminine behaviours; however, they are part of a subculture that valorizes warrior masculinity. I sought to understand the gender expectations of the Montreal extreme metal scene and interpret the contradictions encountered by women in this scene with the help of Schippers’ (2007) theoretical framework on gender. To do so, I conducted 16 individual interviews with women and men who take part in the scene. This research fills a gap in the literature on gender that derives from Connell and Schippers’ writings and addresses issues that the field of metal studies has brushed over. I found that metal men are the “default” participants in the scene. They are expected to be fine music connoisseurs and even become musicians. In contrast, women’s presence is heterosexualized and attributed to a romantic or sexual interest in metal men. Women are suspected of being “poseuses” or groupies with no real interest in the music until proven otherwise. To become legitimate participants, they have to overcome those expectations and prove that they are worthy of being viewed through the prism of masculinity rather than femininity. They do so by proving their exceptionality through manhood acts and distancing themselves from other women. Despite their gender transgressions, women’s presence does not fundamentally question gender relations but reaffirms the overall primacy of masculinity over femininity.
https://spectrum.library.concordia.ca/id/eprint/988125/
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; anthropologie; approches et analyses; discipline; genre; hétérosexisme; masculinité; montréal; mémoires/thèses; privilèges; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; stéréotypes de genre; systèmes d'oppressions; étude qualitative

Examining the cracks in universal water coverage: Women document the burdens of household water insecurity - Radonic, Lucero; Jacob, Cara E. (Water Alternatives, 2021)
L’accès universel à l’eau potable est considéré comme une caractéristique déterminante des villes du Nord global. Cet article décrit les défis quotidiens auxquels sont confrontées les femmes de la classe ouvrière de Flint, dans le Michigan, lorsque la promesse d’une infrastructure d’eau moderne se fissure. En 2014, afin de réduire les coûts, la source d’eau potable de Flint a été transférée du lac Huron à la rivière Flint. Ce changement, et plus particulièrement la manière dont il a été géré, a entraîné une contamination de l’approvisionnement en eau par du plomb et des agents pathogènes. Si l’expérience de Flint est désormais un cas emblématique d’insécurité hydrique dans le Nord global, elle n’est pas unique. À travers une étude de cas élaborée dans le cadre d’un projet de recherche participative communautaire, cet article détaille comment l’insécurité hydrique a transféré la charge de l’approvisionnement en eau potable aux ménages individuels, et plus particulièrement aux femmes. Plutôt que de pouvoir compter sur la main-d’œuvre et l’expertise technique qui ont rendu l’eau potable dans la ville moderne, les habitants de Flint ont été soudainement rendus responsables de la sécurité de leur propre approvisionnement en eau. Nous expliquons comment la crise de l’eau de Flint a fait naître une « nouvelle normalité » ; Nous examinons les façons dont cette situation a donné naissance à un nouveau rapport à l'eau potable, caractérisé par un (re)retour à l'eau en bouteille ou filtrée (de l'eau du robinet) et par un changement dans la répartition des tâches nécessaires à la production d'eau potable. Les témoignages de femmes que nous présentons ici illustrent comment, lorsque l'eau uniforme moderne fait défaut, les gens commencent à voir des eaux hétérogènes.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; accès à l'eau potable; amériques; anthropologie; approches et analyses; capitalisme; discipline; eau en bouteille; environnement; histoire et politique; inégalités hommes-femmes; patriarcat; projet charge mentale; périodes historiques; régions géographiques; santé; sciences humaines; systèmes d'oppressions; thématiques; états-unis

The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'état; violences gynécologiques et obstétricales; états-unis

Structural competency in emergency medicine services for transgender and gender non-conforming patients - Willging, Cathleen; Gunderson, Lara; Shattuck, Daniel; Sturm, Robert; Lawyer, Adrien; Crandall, Cameron (Social Science & Medicine, 2019)
In this formative qualitative research, we draw upon the concepts of structural vulnerability and structural competency to examine how transgender and gender non-conforming (TGGNC) patients and healthcare personnel experience service delivery in Emergency Departments (EDs), and how this experience can be improved upon. Between October 2016 and June 2017, we undertook 31 semi-structured interviews with TGGNC patients (n = 11) and physicians (n = 6), nurses (n = 7), and non-clinical staff (n = 7) in four community-based EDs in New Mexico. Our iterative coding and analysis process resulted in eight sets of findings: (1) reasons why TGGNC patients seek care from EDs; (2) perceptions about and experiences of TGGNC patients; (3) relevance of gender identity and sex at birth; (4) bureaucracy and communication; (5) spatial considerations; (6) preparing providers and staff to care for TGGNC patients; (7) the lack of resources for structural prescriptions; and (8) respect, humanity, and sameness. Findings suggest that structural issues adversely impact the health and wellbeing of TGGNC patients and service-delivery practices in the ED. We describe study implications for training ED personnel and modifying this practice setting to prevent delayed care and ensure appropriate services for TGGNC patients in need of structurally competent emergency medicine.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amériques; anthropologie; discipline; personnes trans*; projet charge mentale; périodes historiques; régions géographiques; santé; sciences humaines; service d'urgences; thématiques; états-unis

Les théories postcoloniales et leurs enjeux pour une anthropologue racisée: quelques éléments de réflexivité - Traoré, Diahara (Le sujet du féminisme est-il blanc? Femmes racisées et recherche féministe, 2015)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; anthropologie; cours; discipline; fem1000; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; études postcoloniales

Bisexual, pansexual, queer: Non-binary identities and the sexual borderlands - Callis, April Scarlette (Sexualities, 2014)
This article focuses on sexualities in the USA that exist within the border between heterosexuality and homosexuality. I first examine the usefulness of applying borderland theory to non-gay/non-straight sexualities such as queer and bisexual. I then give an ethnographic analysis of sexual self-identities on the borders, shedding light on how participants envisioned labels such as ‘pansexual,’ and ‘heteroflexible.’ Finally, I explore the ways that the sexual borderlands became tangible in Lexington, Kentucky at certain events and locations. Throughout, I highlight the ways that the sexual borderland touches on all sexualities, as individuals knowingly cross, inhabit, or bolster sexual identity borders.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amériques; anthropologie; approches et analyses; discipline; identités LGBTQIA2+; périodes historiques; queer; ressource en ligne; régions géographiques; sciences humaines; sexologie; sexualité; thématiques; états-unis; étude qualitative

Le prix à payer pour devenir sujet de droit: la sélection des réfugiés allosexuels au Canada - Ricard, Nathalie (Alterstice, 2011)
Depuis les années 1990, le Canada accepte des réfugiés persécutés en raison de leur orientation sexuelle. Le statut de réfugié est octroyé par les membres de la Commission de l’immigration et du statut de réfugié qui évaluent la preuve de l’orientation sexuelle et de la persécution des personnes demandant asile. Or comment prouve‐t‐on sa sexualité et sa victimisation lorsque l’on a cultivé le silence au sujet de son identité, par peur des représailles, et que le pays d’où l’on vient ne produit pas de documents au sujet de la violence homophobe ? Jusqu’à présent, l’anthropologie ne s’était pas intéressée à la question des réfugiés issus des minorités sexuelles. De leur côté, plusieurs juristes ont cherché à savoir si l’accès à l’asile était équitable pour ces personnes. Les chercheurs se sont peu attardés, toutefois, au langage du droit que ces personnes sont obligées d’utiliser pour se faire reconnaître. Cet article explore les enjeux soulevés par le témoignage des demandeurs et demandeuses d’asile issus des minorités sexuelles, en portant une attention particulière aux exigences du discours juridique qui tend à réifier les dimensions culturelles et sexuelles de la subjectivité. Ainsi, les difficultés de dire la violence ne relèveraient pas uniquement des effets traumatiques de cette dernière, mais aussi du régime d’intelligibilité de la personne qui reçoit le témoignage. Les fonctionnaires canadiens gagneraient à être sensibilisés aux différences culturelles et aux rouages de l’homophobie, à ceux de leur pays comme à ceux dans d’autres sociétés, afin que le processus asilaire soit plus équitable.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amériques; anthropologie; approches et analyses; canada; cours; discipline; droits; identités LGBTQIA2+; justice sociale; migration; minorités sexuelles; premier cycle; périodes historiques; queer; ressource en ligne; réfugiés; régions géographiques; sciences humaines; sex2283; thématiques